Medidas conductuales-sociales y su relación con el covid-19 en pacientes atendidos en el Centro de Salud San Pablo de Atenas durante el periodo abril -agosto 2024. - Romo Carrasco, Samantha Michelle (2024)
The COVID-19 pandemic has led to the implementation of various social distancing and behavioral measures to curb virus transmission. These measures include mask-wearing, physical distancing, limiting social gatherings, and promoting hand hygiene. The effectiveness of these practices and the extent to which individuals adhere to them are crucial for reducing SARS-CoV-2 transmission and mitigating the pandemic’s impact on public health. This study investigates adherence to and perceptions of social distancing measures among different demographic groups. It focuses on how individuals adjust their daily behaviors in response to public health recommendations and identifies challenges and barriers they encounter. Through a survey, data was collected on the frequency of practices such as mask-wearing and physical distancing, as well as perceptions of their effectiveness.